Justice at Redwillow - Nesbitt, John D. (Five Star, a part of Gale, Cengage Learning, 2015)
Jim Fontaine wants to get a new start in life by settling on his own piece of land near the town of Redwillow. He isn't there very long, though, when a saloon girl named Emma turns up dead and a friend of his, Charley Drake, gets thrown in jail for the murder. Nora Winterborne, who is new in town, confides to Fontaine that she is interested in the case because Emma was her sister, but she has to keep quiet. Fontaine also learns of the disappearance of a woman named Judith Deaver and is faced with a trespasser who seems to be looking for something on his homestead. Fontaine has to follow a trail of twisted stories, old crimes, and new murders, including the death of Charley Drake, to help bring about justice at Redwillow.